Online Bakery Shop - Ang, Li Jing (2021)
The outbreak of COVID-19 pandemic has resulted an enormous effect on society all across the world. The mass of the world's population has been prompted to radically change their behavioural patterns with regard to the number of daily activities that they initially considered automatic or ordinary. Governments has implemented different restrictions including stay-at-home orders during the COVID-19 pandemic's peak phase in an attempt to limit the disease's transmission by limiting people's movement. Therefore, online bakery shop is proposed with the development of a mobile-based application for the customers to place orders as well as a web-based management system that helps the bakery shop staff to streamline the management process. The mobile-based application will provide a more convenient and time-saving way for the customers to place orders at anytime and anywhere without having to drive to the bakery shop. It will make the ordering process, which was previously done manually, more simple and faster, since customers will be able to purchase items in seconds as long as they have internet access or a connection. On top of that, a web-based management system will be developed for the staff that streamlines the entire ordering process starting from order placement to final delivery. Hence, bakery shop owner would not have much worries on the day-to-day operations. Also, the staff will be able to make instant, real-time changes to their selling products whereby customers will always get the up-to-date changes. By having this web-based management system, challenges such as mix-ups and misunderstandings in customer orders that often leave customers dissatisfied with their experience can be overcome. Therefore, an online bakery shop is a good solution that beneficial to both the bakery shop staff and the customers.